You are on page 1of 95

# 1

29 2003
:

:
1o
A.

, f
x 0 ,
.
8

;
7

,

.

. z z ,
z = z = z .
2
. f
.
f(x)>0 x ,
f .
2

.
,

f (x)dx = f (x) + c

f,

, c IR .
2

. f
,
f
.
2
. f
x 0 . f
x 0
f(x 0 )=0, f
x 0 .
2
2

z=+i, ,IR
_
_
w=3z i z +4 , z z .

. Re(w)=3+4

m(w)=3.
6
. , w
y=x12 ,
z
y=x2 .
9
2

. z ,

y=x2 , .
10
3

f(x) = x 5 +x 3 +x .

. f
f .
6
. f(e x )f(1+x) xIR.
6
.
f (0,0)
f

f 1.

5
.
f 1, x
x=3 .
8
4
f [,]
(,) .
f() = f() = 0 (,), (,),
f()f()<0 , :

f(x)=0
(,).
8

. 1 , 2 (,) f( 1 )<0
f( 2 )>0 .
9
.
f .
8
( )
1.
(, , ).
.
2.
.
.

.
3. .
4.
.
5. : (3)
.
6. : 10.30 .
K

1

8 2003
:

: (4)

1o
A.

f .
F f ,
:
.

c R

G(x) = F (x) + c ,

f
. G f

G(x) = F (x) + c ,

c R .
10

,

.
. z 1 , z 2 ,
z1 z2 z1 + z2 z1 + z2 .

2
. f '
( , ),
x 0 , f .
f (x) > 0 ( , x 0 ) f (x) < 0
( x 0 , ), f (x 0 )

f.

2
1

. f : R 1 1 ,
x 1 , x 2 A
:
x 1 = x 2 , f(x 1 ) = f(x 2 ) .
2
. f, g
, :

f(x) g (x) dx

## = f(x) g(x) f (x) g(x) dx .

2

x = x 0
f ;
7

2
. ( )
z :

z = 2

m (z) 0 .
12

. , z
() ,

1
4
z +
2
z
xx .

w =

13

3

.

x2 + 1 x .

f(x) =

lim f(x) = 0 .

x+

5
.
f , x .

. f (x) x + 1 + f(x) = 0 .
.

1
2

x +1

dx = ln

( 2 + 1)

6
.
8

4
f IR
, :
f(x) = f (2 x) f (x) 0 x IR .
. f .
8
. f(x) = 0
.
8
.

g(x) =

f(x)
.
f (x)

g
xx, 45 .
9
3

( )
1.
(, , ).
.
2.
.
.

.
3. .
4.
.

5. : (3)
.
6. : 10.00 .
K

27 2004
:

: TE (4)
1o
A.

f '
x 0 . f
x 0
, f(x 0 )=0
10

f
x 0 ;
5

.
.

.
.

lim f(x) = A ,

x x 0

2
lim f(x) = lim f(x) = A

x x
0

x x 0+

2
. f, g x 0 ,
fg x 0
:
(fg)(x 0 ) = f(x 0 ) g(x 0 )
2

. f,
. f(x)>0 x
, f .
2
. f
[,]. G f [,],

f (t)dt = G () G ()
2
2
f f(x)=x 2 lnx .
.

f,

.
10

f
.
8

f.

g(x)=e x f(x),
IR f(0)=f( 3 )=0 .
2

(0, 3 )
2

f()=f().
8

. f(x)=2x 2 3x,

I ()=
.

g(x)dx ,

IR
8

lim I()

9
4
f: IR IR f(1)=1.
x IR,
g(x)=

x3

z f (t)dt 3 z +

1
(x 1) 0,
z

z=+iC, , IR *, :
. g
IR g.
5
. N z = z +

1
z
8

.
1
Re(z 2 ) =
2
6
. A f(2)=>0, f(3)= >,
x 0 (2,3) f(x 0 )=0.
6

( )
1.
(, , ).
.

.
2.
, .
.

,
.
3. .
4. .
5. : (3)
.
6. : 10:30 .
K

1

5 2004
:

: (4)

1o
A.

f .
f
f(x) = 0 x ,

f
.
9
.

,

.
. f x 0
,
.
2

.
.
2
. f, g IR
fog gof,
.
2

. C C
f f 1
y = x xOy
xOy.
2
. f x 0 ,
lim

x x0

## f (x) = k lim f(x) , f(x) 0

x x0

x 0 , k k 2.
2
.

f
(, )
[, ].
6

2
f: IR IR f(x) = 2 x + m x 4 x 5 x ,
mIR, m > 0.
. m f(x) 0 x IR .
13
. m = 10,
f,
xx x = 0 x = 1.
12
3
f: [, ] IR
[, ] f(x) 0 x [, ] z
Re(z) 0, m(z) 0 Re(z) >Im(z).

z +

1
1
= f() z 2 + 2 = f 2 (), :
z
z

. z= 1
11

. f 2 () < f 2 ()
5
. x 3 f() + f() = 0
(1, 1).

4
f [0, +) IR ,
1
x2
f(x) =
+ 2 2xf(2xt) dt .
0
2

f (0, +).
7

f(x) = e x (x + 1).

## f(x) [0, +).

5

lim f(x)

x+

lim f(x) .

( )
1.
(, , ).
.
2.
, .
.

,
.
3. .
4. .
5. : (3)
.
6. : 10:00.
K

31 2005
:

: (4)
1 o
A.1

f,
[, ].
f [, ]
f() f()
f() f()
, x 0 (, ) ,
f(x 0 ) = .
9

.2

y = x +
f +;
4

B.

,

.
. f [, ] f() < 0
(, ) f() = 0,
f() > 0.
2
. lim (f(x) + g(x)) ,
x x0

lim f(x)
x x0

lim g(x) .

x x0

. f f 1
f
y = x,
f 1 .
2
.

x x0

1
=+ .
x x 0 f(x)
lim

2
. f
,
x
x .

## f (t)dt = f(x) - f()

2
. f
,
x
x , .
2
2
z 1 , z 2 , z 3 z 1 =z 2 =z 3 = 3.
9
.
. : z1 =
z1
7
z1 z2
+
.
.
z2 z1
9
1
. : z 1 + z 2 + z 3 =
z 1 z 2 + z 2 z 3 + z 3 z 1 .
3
9

3
f f(x) = e x ,

> 0.

. f .
3
.
f,
, y = ex.
.
7
. () ,
f,
yy,
e -2
.
() =
2
8

2 ()
. lim
+ 2 +

.
7

4
f IR ,
2 f(x) = e x

f(x)

x IR f(0) = 0.

1 + ex
.
. : f(x) = ln
2

6
x

. N :

lim

x0

f(x - t) dt
x

.
6

. :
h(x) =

x
x

2005

x2007
.
f (t)dt g(x) =
2007

h(x) = g(x) x IR .
7
.
(0 , 1).

1
x
2005
x t f (t)dt = 2008

( )
1.
(, , ).
.
2.
, .
.

,
.
3. .
4. .
5. : (3)
.
6. : 10:30 .
K

4

1

6 2005
:

: (4)

1 o
A.1

f f (x) = x .
f (0,+) :
f(x) =

1
2 x

.
9

.2

f:A IR 1-1;

B.

,

.

. ,
f
0, f
.
2
. f
(,) x o.
f (,x o ) (x o ,)
, (xo , f (xo ))

f.
2
1

.
.
2
. f,g fog gof,
fog gof.
2
. z, z
xx.
2
. f
IR *, :

f (x)dx = f (x)dx .
2

2
. z 1 , z 2
z 1 +z 2 =4+4i 2z1 z 2 = 5 + 5i ,
z 1 , z 2 .

10

. A z,w
z 1 3i 2 w 3 i 2 :
i.
z, w , z=w
10
ii. z w.
5

3
f, IR
f(x)0 x IR .
. f 1-1.
7
. C f f
(1,2005) (-2,1),
f 1 ( 2004 + f (x2 8)) = 2 .

9
. C f ,
C f
1
x + 2005 .
(): y =
668
9
4
f: IR IR ,

lim
x0

f (x) x
= 2005 .
x2

. :
i. f(0)=0
4

ii. f(0)=1.

x2 + (f (x))
lim 2
2 = 3.
x0
2x + (f (x))
2

. IR , :

7
. f
IR f(x)>f(x) x IR ,

:
i.
ii.

xf(x)>0 x 0.

## f (x)dx < f (1) .

0

4
( )
1.
(, , ).
.
2.
, .
.

,
.
3. .
4. .
5. : (3)
.
6. : 10.30 .
K

4

27 2006
:

: (4)
1 o
A.1

f,
.
:
f(x)>0 x ,
f .
f(x)<0 x ,
f .
10

.2

f
. f
;
5

B.

,

.
2

. z z = z .
2
. lim
f(x) > 0 ,
xx

f ( x ) > 0

x 0 .
2

. H f()
f
.
2
. (3 x ) = x 3 x - 1 , x IR .
2
.

## f (x)g(x)dx=[f(x)g(x)] f (x)g(x)dx, f,g

[,].
2

2
f(x) =2+(x-2) 2 x2.
. f 1-1.
6
. f -1
f .
8
.

i.

f f -1
y=x.
4

ii.

f f -1 .
7

3
z1 , z 2 , z 3 z1 = z 2 = z 3 = 1
z1 + z 2 + z 3 = 0 .

:
i. z1 z 2 = z 3 z1 = z 2 z 3 .
9
ii. z1 z 2

4 Re (z1 z 2 ) 1 .

8
z 1 ,z 2 ,z 3
,
.
8

4
f(x)=

x+1
lnx.
x1

.
f.
8
. N f(x)=0 2
.
5
.
g(x)=lnx (,ln) >0

h(x)=e x ( ,e ) IR ,
f(x)=0.
9
.
g h
.
3

( )
1.
(, , ).
.

.
2.
, .
.

.
3. .
4.
.
5. : (3)
.
6. : 10.30 .

1

5 2006
:

: (4)

1o
A.1

: (x)=x, xIR .
10

.2

f .
f ;
5

B.

,

.
. z 1 , z 2 , :

z 1 z 2 z1 + z 2 .
2
. f, g x o
f

g(xo)0,
g
xo :

f
(xo ) = o
[g(xo )] 2
g

.
2

. x0 [ln x ] =

1
.
x
2

. f: IR 11,
y
f(x)=y x .
2
. f
[,]. G f [,],

## f(t)dt = G() G() .

2

2
1 + ex
f(x) =
, xIR .
x +1
1+ e
. f
IR .
9

1
dx .
f(x)
9

. x<0 :
f(5 x )+f(7 x )<f(6 x )+f(8 x ) .

3
z,
(4z) 10 = z 10 f f(x) = x 2 +x+, IR .
. z
x=2.
7

()
f x=2
yy y o =3,
i.

().
9

ii.

f, (), xx
3
x = .
5
9
4

1
, x>0 .
x
ii. f
(0,+).

. i.

## : ln(x + 1) lnx <

12
.

1
lim xln(1 + ) .
x +
x
5

(0,+)
(+1) = +1 .
8

( )
1.

2.

3.
4.
5.
6.

(, , ).
.

.

, .
.

.
.
.
: (3)
.
: 10.30 .

24 2007
:

: (5)
1 o
A.1

z 1 , z 2 , :
z1 z 2 = z1 z 2 .

8
.2

f, g ;
4

.3

y = A
f +;
3

B.

,

, ,
, ,
.
. f [,]

## x[, ] f(x) 0 f(x) dx > 0 .

2
. f
x
. f
f(x) > 0 x .
2
1

. f x 0
g x 0 ,
g o f x 0 .
2
. f
,

g(x)
f(t) dt = f (g(x) ) g (x)

.
. > 1

lim x = 0 .

2
2

z=

2 + i
+ 2i

IR .

. z
(0,0) =1.
9
. z 1 , z 2
z=

2 + i
+ 2i

= 0 = 2 .
i.

z 1 z 2 .
8
2

ii. :
(z1 ) 2 = ( z 2 )

.
8
3
:
f(x) = x 3 3x 2 2

IR + , Z.
2
. f ,
.
7
. f(x) = 0
.
8
. x 1 , x 2 x 3
f,
B ( x 2 , f(x 2 ) )

( x 3 , f(x 3 ) )

( x 1 , f(x 1 ) ) ,
2
y = 2x 2 .
3
.

2
f y = 2x 2 .
7

4
f
[0, 1] f(0) > 0.
g [0, 1]
g(x) > 0 x [0, 1].
:
x

x [0, 1],

x [0, 1].

## F(x) = 0 f(t) g(t) dt ,

G(x) = 0 g(t) dt ,

## . F(x) > 0 x (0, 1].

8
. N :
f(x)G(x) > F(x)
x (0, 1].
6
. N :
F(x) F(1)

G(x) G(1)
x (0, 1].

4
. :
x f(t) g(t) dt x 2 t 2 dt
0
0

lim
x0+
x g(t) dt x 5
0

7
4

( )
1.
(, , ).
.
2.
, .
.

.
3. .
4.
.
, .
5.
.
6. : (3)
.
7. : 10.30 .

1

3 2007
:

: (4)

1o
A.1

f
x 0 ,
.
10

.2

B.

Rolle

,

, ,
, ,
.
. f()
f .
2
. f, g, g
[,],

## f ( x )g( x )dx = f ( x )dx g( x )dx .

2

. f
,
x

f ( t )dt = f(x)

x.
2

. f
(,),

(,) = lim f ( x ) = lim f ( x ) .
x

x +

2
. f, g
. f, g
f(x) = g(x) x ,
f(x) = g(x) x.
2
2

3x ,
x

f (x) =
2
x + x + x,

x<0

x 0.

. lim f ( x ) = 3 .
x 0

. f = f
2
x 0 =0, = = 3.
9

. = = 3, f ( x )dx .
0

3

f(x) = e x e lnx,

x > 0.

. f(x)
(1, +).
10
.

f(x) e x > 0.
7

.
x 2 +2

x 2 +1

f ( t )dt =

x2 +2
x 2 +3

f ( t )dt + 2 f ( t )dt

(0, +).
8
4

z 1 = +i z 2 =
, IR 0. z 2 z 1 IR .

2 z1

2 + z1

. z 2 z 1 = 1.
9
. z 1
.
6
.

z1

>0,

z 1

## (z1 + 1 + i)20 (z1 + 1 i)20 = 0 .

10

1.
2.

3.
4.
5.
6.
7.

( )
(,
, ).
.

, .
.

.
.

. ,
.
.
: (3)
.
: 10.00 .
K

24 2008
:

: (5)
1 o
A.1

f(x) = ln x , x*
* :

( ln x ) =

1
x

10
.2

f
[,];
5

B.

,

, ,
, ,
.
. f:A 11,
f 1 :
f 1 ( f ( x ) ) = x, x A f ( f 1 ( y )) = y, y f ( A )
2
. f

f
.
2
1 5

. z 2 +z+=0
,, 0 ,
.
2
. f
,

f( x ) > 0
x.

. A f ,,

## f(x)dx = f(x)dx + f(x)dx

z w
(i + 2 2 )z = 6

w (1 i) = w (3 3i)

:
.
z .

.
w .

6
.

zw

6
2 5

3
x lnx , x > 0
f(x) =
0 , x=0

. f 0.
3
. f
.
9
.

x = e .
6
.
f(x+1)>f(x+1)f(x) ,
x > 0 .

4
f
2

.
f(x)=20x 3 +6x45
8

3 5

.
g(x) g(x h)
h 0
h

g(x) = lim

4
. f ()
g ()
lim

## g(x + h) 2g(x) + g(x h)

h2

h 0

g(0)=g(0)=1,

= f(x) + 45

i. g(x)=x 5 +x 3 +x+1
10
ii. g 11

( )
1.
(, , ).
.
2.
, .
.

.
3. .

4 5

4.
.
, .
5.
.
6. : (3)
.
7. : 10.30 .
K

5 5

3 2008
:

: (4)
1o
A.

[, ].
G f [, ],

f ( t )dt = G () G ( )

10
.

;
5

,

,
, ,
.
. 11,
.
2
. f ,
f

,
.
2
.

f ( x )dx

1 4

xx
xx.
2
. , , :
+i=0 =0 =0
2
.
(, x )(x , ) A
. :
lim f(x) = A lim (f(x) A ) = 0
x xo

x xo

2
2
1+ i 3

2
z 2 +z+=0, .

z1 =
. =1 =1.

9
. z13 = 1.
8
.
w, :

w = z1 z1

2 4

3
f(x) = x 2 2 ln x, x > 0.
. : f(x)1 x>0.
6
.
f.
6
.

ln x

f (x)
g( x ) =

i.

, x >0
, x=0

k g
.
6

1
ii. k = , g ,
2
, (0, e).

7
4
f [0, + )
f(x) > 0 x 0. :
F(x) =
h(x) =

f(t) dt ,

F( x )

x
0

x [0, + ),

x (0, + ).

t f ( t ) dt

3 4

1
0

## e t 1[f ( t ) + F( t )]dt = F(1)

6
.

(0, + ).

8
. h(1)=2, :
i.

2
0

f(t) dt < 2

tf(t)dt
0

6
ii.

1
0

1
F( t ) dt = F(1)
2

1.
2.

3.
4.
5.
6.
7.

(, , ).
.

, .
.

.
.

. ,
.
.
: (3)
.
: 10.00 .

K

4 4

( )
20 2009
:

: (5)

1 o
. f .
f x
f ( x ) = 0 , f
.
10
. f
x 0 ;
5
. ,

,
, ,
.
.

z 1 , z 2 ,
z1z 2 = z1 z 2

2
.

f
() x 0 A,
f(x)f(x 0 ) xA
2
1 5

x 1
=1
x 0
x
lim

2
.

f

.
2

f
[, ] f(x)<0 x[, ],

f, x=, x=
xx
( ) =

f (x )dx
2

2

z=(2+1)+(21)i ,

..
z,

9
.

z 0 = 1 i
.
8

2 5

w + w 12 = z 0
z 0
.
8
3

f (x) = x ln( x + 1),
> 0 1

x > 1,

A. f ( x ) 1 x > 1, =e
8
. =e,
. f .
5
. f
(1, 0]
[0, + )
6
. , (1, 0) (0, + ) ,
f () 1 f ( ) 1
+
=0
x 1
x2

(1, 2)

3 5

4
f [0, 2]

2

0 (t 2)f (t )dt = 0

H( x ) =

0 t f (t )dt,

x [0, 2],

x
H( x )

f
( t )dt + 3,
x
0

G(x) =
1 1 t2

,
6 lim
t 0
t2

x (0, 2]
x=0

. G
[0, 2].
5
. G
(0, 2)
G( x ) =

H( x )
x

0<x<2

6
. (0, 2)
()=0.
7
. (0, )

t f ( t )dt = 2

0 f (t )dt
7

4 5

1.
(, , ).
.
2.
, .
.

.
3. .
4.
.
5.
.
6. : (3)
.
7. : 10.00 ..
K

5 5

9 2009
:

: (5)
1 o
A.

f(x) = x . f
(0 , + ) :

f ( x ) =

1
2 x
9

B.

f x o
. f x o ;
6

,

,
, ,
.
.

( z ) = ( z )
2

. f 1-1,

f .
2

1 5

## . lim f(x) = 0 f(x) < 0 x o

xx o

lim

xx o

1
= +
f (x)

2
. f(x) = x. H f
1 = { x x = 0 }

f ( x ) = -

1
2 x

2
.
,

f,

f (x) dx = f(x) + c,

c .
2
2
z
:

(2 i ) z + (2 + i ) z 8 = 0
. N
z = x+yi
.
10

2 5

. N z1
z 2
.
8
. z1, z 2
z1 + z 2

+ z1 z 2

= 40

7
3

## f(x) = ln[(+1)x 2 +x+1] - ln(x+2),

x > -1

-1
. ,
lim f(x) .
x +

5
. = -1
.

f
.
10

f
6

. f(x) + 2 = 0

0
4

3 5

f: [0 , 2]

f ( x ) 4 f ( x ) + 4 f ( x ) = k x e 2 x , 0 x 2

## f (0) = 2 f (0) , f (2) = 2 f(2)+12 e 4 , f(1) = e 2

k .
.

f ( x ) 2 f ( x )
, 0 x 2
g(x) = 3x 2 e2x
Rolle
[0,2].
4
(0,2) ,

f ( ) + 4 f ( ) = 6 e 2 + 4 f ( )
6

k = 6 g(x) = 0
x [0,2].
6

f ( x ) = x 3 e 2 x , 0 x 2
5

f (x)
x2

dx

4 5

1.
(, , ).
.
2.
, .
.

.
3. .
.
4.
.
,
.
5.
.
6. : (3)
.
7. : 10.00 ..
K

5 5

( )
19 2010
:

: (4)

A1. f .
F f ,
:

G(x)=F(x)+c,

G f

G(x)=F(x)+c,

6
A2. x=x 0
f ;
4
A3. f
. f
;
5
4. ,

,
, ,
.
)
+i +i
.
1 4

) f
. f
,
.
) f
(,),

(,),
A = lim +f ( x ) B = lim f ( x )
x

) (x)=x, x
) lim f ( x ) < 0 , f(x)<0 x 0
xx 0

10

2
= 2 zC z0
z
B1. z 1 z 2 .

z+

B2.
z12010 + z 2010
=0
2

B3. w

w 4 + 3i = z1 z 2

w
.
7
B4. w 3,
3 w 7
5
2 4

f(x)=2x+ln(x 2 +1), x
1. f.
5

2. :

(3x 2) 2 + 1
2 x 3x + 2 = ln

4
x
+
1

7
3. f
f
.
4.

I = xf ( x )dx
1

f: x
:
f(x) x
x

f(x)x =3+

t
dt
f (t) t

1. f

f(x)=

f (x)
, x
f (x) x

5
2. g(x)= (f ( x ) )2 2xf(x),
x, .
7
3 4

3.
f(x)=x+ x 2 + 9 , x
6

4.
x +1

x+2

## f (t)dt < f (t)dt ,

x

x +1

7

1.
(, , ).
.
2.
, .
.

.
3. .
4.

.
5.
.
6. .
7. : (3)
.
8. : 10.00 ..
K

4 4

7 2010
:

: (5)

A1. f(x) = x, x,
( x ) = x
8
A2. f
[,] ;
4
A3. f
x 0 A () , f(x 0 );
3
4. ,

,
, ,
.

( )

) f(x) = x , > 0, x = x x 1

) f o g g o f,
f o g = g o f
) lim f ( x ) = + , lim
xx 0

x x 0

1
=0
f (x)

1 5

) f
[,] f(x) 0 x[,],

f (x)dx 0

) zC z = z z
10

z 1 , z 2

z 1 +z 2 = 2 z 1 z 2 = 5
B1. z 1 , z 2
5
B2. w
2

w z1 + w z 2

= z1 z 2

w
(x+1) 2 + y 2 = 4
8
B3. w 2

2 Re(w) + Im(w) = 0
6
2 5

B4. w 1 , w 2 w

w1 w 2 = 4 ,

w 1 + w 2 = 2
6

f(x) = (x2)lnx + x 3, x > 0
1.
f
5
2. f
(0,1] [1, + )
5
3. f(x) = 0
.
6
4. x 1 , x 2 3 x 1 < x 2 ,
(x1, x2) ,

f() f() = 0

f (, f () )
.
9

3 5

f:
f(0) = 1 f(0) = 0
1. f(x) 1 x
4
1

x f ( xt )dt + x 3
0

2. lim

x0

= +
6

f(x) + 2x = 2x f ( x ) + x 2 , x, :

3.

f(x) = e x x 2 ,

x
8

4.
x +2

h(x) =

f (t)dt , x 0
x

x 2 + 2x +3

x 2 + 2 x +1

## f (t)dt + f (t)dt < 0

4 5

1.
(, , ).
.
2.
, .
.

.
3. .
4.

.
5.
.
6. .
7. : (3)
.
8. : 09.30 ..
K

5 5

( )
16 2011
:

: (4)

A1. f
x 0 . f
x 0
, : f (x 0 ) = 0
10
A2. f .
y=x+
f + ;
5
A3. ,

,
, ,
.
) z 0 z 0 =1
) f:A 1-1,
x 1 , x 2 A :
x 1 x 2 , f(x 1 ) f(x 2 )
) x 1 ={x|x=0} : (x ) =
) :

x
=1
x + x
lim

1 4

1
2 x

) C C
f f 1 y=x
xOy xOy.
10

z w z 3i ,
:

z 3i + z + 3i = 2 w = z 3i +

1
z 3i

B1.
z
7

B2. z + 3i =

1
z 3i
4

B3. w
2 w 2
8
B4. :

zw = z
6

f : ,
, f (0 ) = f (0) = 0 , :
e x (f ( x ) + f ( x ) 1) = f ( x ) + xf ( x )

x.

2 4

1. : f ( x ) = ln(e x x ), x
8
2. f
.
3
3. f
.
7
4. ln(e x x ) = x

0,
2
7

f, g : ,
x :
i)
ii)

iii)

f(x)>0 g(x)>0

1 f (x)
e2x
1 g( x )

2x

e2t
dt
g(x + t )
e2 t
dt
f (x + t)

1. f g
f(x) = g(x) x .
9
2. :
f(x) = e x , x
4
3 4

3. :

lim

x 0

ln f ( x )
1
f
x

5
4.

F( x ) =

f ( t 2 ) dt

xx yy x=1.
7

1.
2.

3.
4.
5.
6.
7.
8.

( )
(,
).
.

.
.
.
.

. ,
.
.
.
: (3)
.
: 10.00 ..

4 4

6 2011
:

: (5)

A1. f(x)=x
x
( x) = x
10
A2. f, .

f .
5
3. ,

,
, ,
.
) z=+i, ,
z z =2
) f
x 0 A () f(x 0 ),
f(x) f(x 0 ) xA
) f
, 1-1 .

1 5

lim f ( x ) = 0

xx 0

f(x)>0

x0,

1
=+
x x 0 f (x)
lim

) f
x 0
.
10

z, w,
:
z i =1+Im(z)

(1)

## w( w +3i )=i(3 w +i)

(2)

B1.
z
1
4

y= x 2
7

B2.
w
(0,3) =2 2 .
7
B3. ,
z, w
z =w.
5
B4. N
, ,
u ,
2 5

,,, .
6

y= x , x 0 .
(0,1)
xy
, .
y

y= x
(4,2)

(0,1)

t, t 0 x(t ) = 16 m/min
1. ,
t, t 0 :
x(t)=16t
5
2.
(4,2)
, ,
.
6

3 5

3.

.
6
1
4

4. t0 (0, ),
d=()
.
8

xy.

f: , 3
, :
i) lim

x 0

f (x)
= 1 + f (0)
x

## ii) f(0) < f(1)-f(0)

iii) f (x ) 0

1.
f
x 0 =0.
3
2. f .
5
g(x)=f(x)x, x , :
3. g
x
x 0 xg ( x )

lim

6
4 5

4.

f (x) dx >2
0

5
5.
g, x x
5
2

1

f (x) dx
0

(1,2)
,

f (t) dt = 2
0

6
1.
2.

3.
4.
5.
6.
7.
8.

( )
(,
).
.

.
.
.
.

. ,
.
.
.
: (3)
.
: 18.00
K

5 5

( )
28 2012
:

: (4)

A1. f
. f(x) > 0 x
, f

7
A2. f
[, ];
4
A3. f .
f x 0 A ;
4
A4. ,

,
, ,
.
)

) f 1-1,
y f(x)=y
x
)

## lim f (x) = +, f(x)<0 x 0

x x 0

1 4

) (x) =

1
2 x

, x{x|x=0}

f(x)g(x)dx =

[f(x)g(x)]

+ f(x)g(x)dx, f, g

[,]

10

z w
:
2
2
z_1 + z + 1 = 4
w_5 w = 12

(1)
(2)

B1.
z
= 1
6
B2. z 1 , z 2
z z1 _z2 = 2 , z1 + z2 .
7
B3.
w
x2
y2
+
= 1

9
4
w
6
B4. z,w
(1) (2) :

1 z w 4
6
2 4

## f(x)=(x1) ln x1, x>0

1. f
1 =(0,1]
2 =[1,+ ).
f
6
2.
.

xx-1 = e 2013 ,

x>0
6

3. x 1 , x 2 x 1 <x 2
2, x 0 (x 1 ,x 2 )
,
f(x0 ) + f(x0 ) = 2012
6
4.
g(x)=f(x)+1
x>0, xx x=e
7

f:(0,+ ) ,
x>0 :
f(x) 0
x 2 x +1

x x2
f(t)dt
e
1

ln xx =

lnt t
dt + e f(x)

f(t)

1. f
.
10
3 4

1

lim (f (x))2
f (x)
+
f (x)

x 0

2. :

5
3. ln xx1,
x>0,

F(x) =

## f(t) dt, x>0,

>0, ( 2).
:
F(x) + F(3x) > 2F(2x), x>0 ( 4).
6
4. >0.
(,2) :

## F() + F(3) = 2F()

4
( )
1. ( ,
). .
2.
.
.
.
3. .
4. .
,
.
5. .
6. .
7.
:

(3)

.
8. : 10.30 ..

4 4

14 2012
:

: (4)

A1. f (, ),
x0, f
. f(x)>0 (, x0) f(x)<0 (x0, ),
f(x0) f
7
A2. f g ;
2
3. Rolle.
6
4. ,

,
, ,
.
) f
, xx,
f
)
+i +i
.
) 0<<1,

lim x = +

x +

) f
x 0 , x 0
1 4

) f
[, ]. G f [, ],

## f (t)dt = G() G()

10

z, z1,
w=

z 1
.
z +1

:
B1. z = 1
7
4

B2. z .
z

6
1 1
B3. + (z 1 +z 2 )4, z 1 , z 2
z1 z 2
z

6
B4. u,
i
uui= w, w0, x 2 y 2 =1
w
6

f: , :

xf(x)+1=e x , x .

2 4

ex 1

, x0
1. f(x)= x
1
, x=0

6
2. o f1
.
6
3.
f (0, f (0) ) . ,
f ,

2f(x)=x+2, x
.

4. lim+ [x (lnx ) ln (f ( x ) )]
x 0

f:A =(0,+ ),
:
f(A)= ( , 0]
f (0,+ ),
1

2f(x)+ x + e f ( x ) =
x

1
e f ( t ) f ( t ) t + dt + 2, x>0
t

F(x)=

f ( t ) dt , x>0

2x
1. f(x)= ln 2 , x>0
x +1

8
3 4

2. F
(x 0 , F( x 0 ) ) , x 0 >0,
.
(x0, ) >x0,
F M (, F( ) )

3. >1,

## [F() + (1 ) f ()] x 5 + ( 1) ( x + 1)3 = 0

x 1
x 3
, x, (1,3)
5

4 .
x2

t
f dt t f ( t ) dt , x > 0
x
1

6
1.
2.

3.
4.
5.
6.
7.
8.

( )
( ,
). .

.
.
.
.
.
,
.
.
.

(3)

.
: 18.30
K

4 4

1

( )
27 2013 - :

: (4)

A1.

[ , ] .

f , , :

f ( t ) dt = G ( ) G ( )
7

A2.

A3.

(...)
4
f
, ;

4
A4.

,

, , ,
.

z z0 = , >0

( )

K z0

, z, z0 .

## ) lim f ( x ) < 0 , f ( x ) < 0 x 0

x x0

) :

x x x
x 1
=1
x 0
x

) : lim

) f
f
.
10

1 4

2

z :

( z 2)( z 2) +
B1.

z2 = 2

z ,
K ( 2,0 ) = 1
( 5)
, z
, z 3

( 3)
8

B2.

z1, z 2
w + w + = 0 , w ,
, ,
2

Im ( z1 ) Im ( z 2 ) = 2
:

= 4

=5
9

B3.

0 , 1, 2
1. v
:

v 3 + 2 v 2 + 1v + 0 = 0
:

v <4
8

f,g :
:

( f ( x ) + x ) ( f ( x ) + 1) = x ,

f ( 0 ) = 1

3x 2
g( x) = x +
1
2

2 4

3
1.

f ( x ) = x2 + 1 x , x
9
2.

f ( g( x)) = 1
8
3.

x 0 0,

, :
4

f ( t ) dt = f x 0 x 0
4

x0
4

f : ( 0, + )

f (1) = 1

lim
h 0

( 0, + )

f (1 + 5h ) f (1 h )
=0
h

g( x) =

f (t) 1
dt ,
t 1

x (1, + ) > 1

:
1.

f (1) = 0 ( 4), f
x 0 = 1 ( 2).
6

2.

g ( 3), ,

8x2 + 6

g(u)du >
8x2 + 5

2x 4 + 6

g(u)du

( 6)

2x4 + 5

3 4

4
3.

g ,

( 1)

f (t) 1
dt = ( f ( ) 1) ( x ) ,
t 1

x>1

.
10

( )
1.

2.

3.
4.
5.
6.

.
- .
-
.

.

.
.
.

. ,
, .
.

:

(3)

.
: 1 0 . 0 0 . .

4 4

1

13 2013
:

: (5)

A1.

f x 0 ,

f .
A2.
A3.

A4.

Fermat.
4
f .
f ;
4
,

, , ,
.
) z z = z
( 2)
) f 11 ,
f
.
( 2)
) lim f ( x ) = ,
x x0

lim ( f ( x ) ) = +

x x0

( 2)
) f , g x 0
:

( f g) ( x0 ) = f ( x0 ) g ( x0 ) f ( x0 ) g ( x0 )
( 2)
) f
, f .
( 2)
10

1 5

2

z, w

2 x 2 w 4 3i x = 2 z , x \
, x = 1
B1.

z
1 = 1,
w
(4,3) 2 = 4
8

B2.

N ,
.
5

B3.

z , w 1
:

z w 10

z + w 10
6

B4.

z 1
, :

2 z2 3 z 2 zz = 5
6

f :

2x f ( x ) + x 2 ( f (x) 3 ) = f (x) x

f (1) =

1
2

2 5

3
1.

x3
f ( x) = 2
,
x +1

6
2.

f
1.
4

3.

## f ( 5(x 2 + 1)3 8 ) f ( 8(x 2 + 1)2 )

7
4.

, , ( 0, 1) , :

f ( t ) dt = ( 3 2 1) f ( 3 )

f : [ 0, + ) ,

0, + ) , :
x

f ( x) = x +

u
1

( f ( t))

f (t)

f ( x ) f ( x ) 0 x > 0

dt du

x > 0

f ( 0 ) = 0

g(x) =

f ( x)
f ( x)

x > 0

h( x) = ( f ( x))

3 5

x 0

4
1.

N :

f ( x ) f ( x ) + 1 = ( f ( x ) )

x > 0
4

2.

. f f

( 0, + )
( 4)

. f ( 0 ) = 1
( 3)
7
3.

( 0, + ) ,

:
.

g( x) 2 x

x ( 0, + )
( 2)

2 x ) f ( x ) dx < 1

( 4)
6

4.

h , xx x = 0

x =1
8

( )
1.

2.

.
- .
-
.

.

.
.
.

4 5

5
3.
4.
5.
6.

. ,
, .
.

:

(3)

.
: 1 8 : 0 0

5 5